2008
DOI: 10.3354/ab00073
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of membrane lipids in gills of adult hard clam Mercenaria mercenaria during declining temperature

Abstract: In a previous study, a major remodeling of lipids, consistent with the theory of homeoviscous adaptation, was observed in the juvenile hard clam Mercenaria mercenaria during a temperature reduction from 24 to -1°C. In addition, the lipid remodeling varied between genetically distinct lines of hard clams. The present study examined whether adult hard clams originating from different locations and a selectively bred variety show differences related to their genetic characteristics in the remodeling of lipids tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 29 publications
(34 reference statements)
3
36
0
Order By: Relevance
“…Ectotherms can counteract the ordering effects of reduced temperature or increased pressure by changing the structure of their membranes [65,66], a process known as homeoviscous adaptation [67]. This biochemical adaptation involves remodeling membrane lipids: changes in phospholipid to sterol ratios and acyl chain length and saturation have been observed in bivalves and finfish [68,69]. Hard clams in Atlantic Canada increased the level of unsaturation of fatty acids in their gills throughout the fall and then increased their phospholipid to sterol ratio in December [68].…”
Section: Membrane Fluiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Ectotherms can counteract the ordering effects of reduced temperature or increased pressure by changing the structure of their membranes [65,66], a process known as homeoviscous adaptation [67]. This biochemical adaptation involves remodeling membrane lipids: changes in phospholipid to sterol ratios and acyl chain length and saturation have been observed in bivalves and finfish [68,69]. Hard clams in Atlantic Canada increased the level of unsaturation of fatty acids in their gills throughout the fall and then increased their phospholipid to sterol ratio in December [68].…”
Section: Membrane Fluiditymentioning
confidence: 99%
“…This biochemical adaptation involves remodeling membrane lipids: changes in phospholipid to sterol ratios and acyl chain length and saturation have been observed in bivalves and finfish [68,69]. Hard clams in Atlantic Canada increased the level of unsaturation of fatty acids in their gills throughout the fall and then increased their phospholipid to sterol ratio in December [68]. Although it is generally accepted that ectothermic animals increase membrane content of unsaturated fatty acids in response to cold to maintain fluidity [70], few studies have shown a clear and direct relationship between unsaturated fatty acids and membrane fluidity in marine organisms [67,71].…”
Section: Membrane Fluiditymentioning
confidence: 99%
“…We speculate that higher observed F 2 IsoPs in Icelandic A. islandica may be the result of higher total lipid uptake in the Icelandic environment. Many clams get most of their polyunsaturated fatty acids from their diets (Langdon and Waldock 1981;Parent et al 2008), and Icelandic A. islandica may have a richer available diet than Baltic Sea A. islandica (Ridgway and Richardson 2010). Analyses and comparisons of lipid and proteome compositions of the two investigated A. islandica populations could give more insights into underlying mechanisms of lipid peroxidation and protein stability.…”
Section: Discussionmentioning
confidence: 99%
“…In S. balanoides, cyprid size increases towards colder regions over continental scales (Crisp 1962). In other organisms, cholesterol responds negatively to temperature as part of a mechanism to regulate membrane fluidity (Crockett 1998), and studies in marine species have found seasonal or spatial patterns in cholesterol that are consistent with the existence of such mechanisms (Parent et al 2008). However, we did not find consistent evidence of latitudinal thermal gradients in the studied area (Fig.…”
Section: −1mentioning
confidence: 97%